Innentitelbild: Synthesis and Degradation of Vinyl Polymers with Evenly Distributed Thioacetal Bonds in Main Chains: Cationic DT Copolymerization of Vinyl Ethers and Cyclic Thioacetals (Angew. Chem. 4/2023). (14th December 2022) - Uchiyama, Mineto; Murakami, Yukihiro; Satoh, Kotaro; Kamigaito, Masami
Abstract : Degradable vinyl polymers are synthesized with periodically arranged in‐chain thioacetal bonds via cationic degenerative chain‐transfer copolymerization of vinyl ethers with a seven‐membered cyclic thioacetal, as reported by Mineto Uchiyama, Masami Kamigaito, and co‐workers in their Research Article (e202215021) . The copolymers can be degraded into low‐ and controlled‐molecular‐weight polymers via hydrolysis.